Antimicrobial Activity of Chemically modified Activated carbon of Tribulus terrestris - krishnasamy, KARTHIK (Research in Biotechnology, 2015)
A weed is a collective term given to plants that grow and compete with the cultivated crops and are found to be resistant to most of the microbial diseases when compared to the cultivated crops. Activated carbon (AC) has been widely used in wastewater treatment for the removal of various pollutants because of its large surface area and high adsorption capacity. It also possesses antibacterial activity to kill air- or water-borne bacteria. In this present study the antimicrobial activity was studied by using Tribulus terrestris weed modified as activated carbon using conc. H2SO4. The activities were determined using agar well diffusion method on the following species of bacteria, i.e., Bacillus subtilis, Escherichia coli, Staphylococcus aureus and Klebsiella pneumoniae. The results showed that activated carbon prepared from Tribulus terrestris possess maximum antibacterial activity against the tested bacterial species.